The Impact of a Computerized Potassium Alert on Adverse Drug Events and Pharmacists' Interventions - Mansour, Hanine (2010)
Background: Hyperkalemia is one of the most common drug-related electrolyte abnormalities resulting in adverse drug events (ADEs) at our institution. Objective: To determine the effect of a computerized pharmacy alert on the number of adverse events related to hyperkalemia in a hospital setting and to study the impact of guidelines and education on pharmacist response to high potassium levels. Methods: An alert was built into the pharmacy computer system, which warned pharmacists about a potassium level greater than 5.1 mEq/L when processing an order that could increase potassium. The alert was linked to a trigger medication list. After the alert was implemented, the number of ADEs due to hyperkalemia was compared for the 3 months pre- and postalert. Due to a lack of consistency in pharmacist interventions after implementation of the alert, hyperkalemia management guidelines were developed by the pharmacy department. The staff pharmacists received training on how to address hyperkalemia when processing prescriptions. After the education component was completed, the types of pharmacist interventions made pre- and posttraining were also compared. Results: Building an automated pop-up alert resulted in a decreased number of ADEs related to hyperkalemia (p < 0.001) and reduced the utilization of medications needed to treat hyperkalemia (p = 0.019). Conclusions: Implementation of a computerized pharmacy alert resulted in a statistically significant decrease in adverse drug events related to hyperkalemia in our institution. Educating pharmacists about hyperkalemia and developing guidelines for its management provided consistency among responses to the high potassium computerized alert. Further studies are needed to evaluate the impact of guideline development and pharmacist education on the trend of drug-induced hyperkalemia in an inpatient pharmacy setting.